2008
DOI: 10.1086/524952
|View full text |Cite
|
Sign up to set email alerts
|

Offspring Size Plasticity in Response to Intraspecific Competition: An Adaptive Maternal Effect across Life‐History Stages

Abstract: When provisioning offspring, mothers balance the benefits of producing a few large, fitter offspring with the costs of decreased fecundity. The optimal balance between offspring size and fecundity depends on the environment. Theory predicts that larger offspring have advantages in adverse conditions, but in favorable conditions size is less important. Thus, if environmental quality varies, selection should favor mothers that adaptively allocate resources in response to local conditions to maximize maternal fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
288
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(309 citation statements)
references
References 66 publications
14
288
6
1
Order By: Relevance
“…Egg weight of middle season females could not be estimated, but it may be assumed that their weight was similar to that of late females, since larval dry weight did not differ between these females. In general, the production of large eggs reflects an enhanced maternal energy investment at the cost of reduced fecundity (Allen et al 2008). In this species, by contrast, the increased fecundity of middle season females without a reduction in egg size (and presumably in weight) and without increasing their reproductive output suggests a better body condition.…”
Section: Discussionmentioning
confidence: 89%
“…Egg weight of middle season females could not be estimated, but it may be assumed that their weight was similar to that of late females, since larval dry weight did not differ between these females. In general, the production of large eggs reflects an enhanced maternal energy investment at the cost of reduced fecundity (Allen et al 2008). In this species, by contrast, the increased fecundity of middle season females without a reduction in egg size (and presumably in weight) and without increasing their reproductive output suggests a better body condition.…”
Section: Discussionmentioning
confidence: 89%
“…1996; Allen et al. 2008) offspring size and survival. Plaistow and Benton (2009) concluded that maternal effects in high competition population (low food ration) impact more on juvenile survival compared with low competition populations (high food ration), where maternal effects have more impact on the population growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive plasticity may be expressible only by reduction in reproductive effort that, as indicated above, is probably mediated in one of (or a combination of) the three ways: (1) via a reduction in the number of follicles recruited into vitellogenesis (that is, reduced clutch size) as body size/energy content declines, (2) via a longer interclutch interval or (3) by earlier cessation of reproduction (produce fewer seasonal clutches). If fluctuations in adult ration are mirrored by reductions in fry ration (via density effects, for example; Allen et al, 2008), this means that fry fitness would also be reduced as the environment now requires a larger fry while, in addition, clutch size is also reduced-a double hit to within-season fitness. Thus, the principal fitness benefit of life-history plasticity must be survival to reproduce in a subsequent Figure 9 Matrix plot showing the relationships between female life-history traits, body mass and somatic condition in Big Beaver Lake, Alaska.…”
Section: Plasticity Within An Overall Life Historymentioning
confidence: 99%